The management of chaotic systems - Gordon, Theodore
Previous papers have described the chaotic nature of nonlinear systems under some conditions : widely fluctuating and randomly appearing behavior, high sensitivity to initial conditions, and "attraction" to a regular trajectory in transformed space. This work has served to demonstrate for planners and policy analysts as well as physical scientists that attempting to forecast the precise future state of a chaotic system may be futile. Yet if the real world is basically nonlinear, then problems of control and management must be faced. This article is an attempt to begin to address this issue. First, we construct a simple social model that can exhibit chaos under some conditions. Then we ask what can be done by a manager to reach hypothetical goals despite the fact that the system he or she is trying to control is in chaos. We find some rules of thumb that may have general applicability to management and introduce some ideas for further study.